Hubungan antara Faktor Demografi dan Kecenderungan Keusahawanan di Kalangan Pelajar UTHM - Yazid, Nadiatul Naqiah; Abu Seman, Noor Aslinda (Research in Management of Technology and Business, 2020)
In recent years, many people want to venture into business. There are many demographic factors that can influence entrepreneurial tendencies among students. This study aims to identify the level of entrepreneurial tendencies among students and examine the relationship between demographic factors and entrepreneurial tendencies among students at UTHM. This study was conducted using quantitative methods and only focused on students in the Faculty of Technology and Business Management (FPTP). A total of 234 students were selected as the study sample. Questionnaire forms were used as research instruments. The data collected were analyzed using Statistical Package for Social Science (SPSS) software using descriptive analysis techniques, Mann-Whitney U and spearman correlation analysis. The results of this study found that the level of entrepreneurial tendencies among students is at a moderate level and there is a significant difference between the relationships of demographic factors namely gender, course of study and family background in influencing entrepreneurial tendencies. From the study that has been conducted, it is found that students have an entrepreneurial tendency through the factors of course of study. If more focus, encouragement and exposure are given to them, the probability for them to become entrepreneurs after graduation will be higher.